REGULATION AND THE FUTURE OF CRYPTOCURRENCY IN INDONESIA - Susilowardhani Susilowardhani; Ashinta Sekar Bidari; Reky Nurviana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Cryptocurrencies is generally used as means of payment and assets. Every country in the world has its own approach in regulating the use of cryptocurrencies. In Indonesia, the use of cryptocurrency as a means of payment is not justified. Meanwhile, its use as an asset is the subject of commodity futures trading whose mechanism is carried out by the existence of an agreement and its activities by Badan Pengawas Perdagangan Berjangka Komoditi (Bappebti). The potential for cryptocurrency growth in Indonesia can be maximized considering the advantages it offers, such as easy access, security, and financial inclusion that can help equalize access to quality formal financial services on time, smoothly, and safely at affordable costs according to the needs and abilities in improving people's welfare. In order to encourage the positive growth of cryptocurrencies in Indonesia, the government as the regulator must ensure the realization of cryptocurrencies that are safe, structured, and stable. Keywords: Cryptocurrency, potency, regulation